Rumi and the Advancement of Man and Society - Merican, Ahmad Murad (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2012)
This paper picks up on Jalaluddin Rumi as a storyteller about man and the universe in relation to the advancement of man and society. It seeks to reflect on Rumi as a human being, embedded in a history and a geography, and the implications of Rumi’s views on today’s world. Rumi sees the Universe as organic, intelligent and sacred. Man is that microcosm. It is important not only to intellectually reflect and spiritually imbue those values in our individual self, but also our collective self, community, nation and civilization. We almost always tend to detach the Rumi corpus from our daily self. This paper argues that the thoughts of Rumi can be a significant source for policy and planning on what we call development. Indeed, Rumi ‘devolutionist’ philosophy brings profound lessons for the construction and advancement of the nation and the nation states in today’s world.